Effects of mycorrhizal fungi on quantitative and qualitative characteristics of Anise plant (Pimpinella anisum) under salt stress - AF Masomi Zavarian; M Yousefirad; M Asghari (Institue of Medicinal Plants, ACECR, 2015)
Introduction: Salinity is one of the most important factors limiting growth and crop production. Mycorrhizal fungi as a biological fertilizer provides food needs plants and can be useful in decrease the effects of stresses on plants. Objective: Improving quantitative and qualitative traits of anise plant using mycorrhizal fungi under salt stress. Methods: This study was done in greenhouse of the research farm of the Islamic Azad University (Saveh branch) as factorial based on randomized complete blocks design. The first factor was mycorrhiza inoculation in three levels of non-inoculated, inoculated with Glomus intraradices strain and inoculation by Glomus mosseae strains and second factor was salinity in three levels control or non-saline water, salinity 50 Mm and 100 Mm. Results: The interaction of salinity and mycorrhiza was significant on the number of seeds per plant, Essential oil percentage of seed and K concentration in leaves (P<0.01), plant height, plant dry weight, number of umbels per plant, number of shed in the umbrella, number of seeds in the shed and sodium concentration in leaves (P< 0.05). Increasing soil salinity decreased all the studied traits, So that greatest damage was observed at 100 Mm salt. Of course salinity decreased sodium concentration of leaves. Also mycorrhizal inoculation improved all the studied traits in the saline and control condition than non inoculated plants. Conclusion: Study results showed mycorrhizal inoculation with both strains improved plants growth and essential oil of anise in salinity conditions, and Glomus mosseae strain was better on anise than Glomus interaradices strain.